Simultaneous HPLC Determination of Methocarbamol, Paracetamol and Diclofenac Sodium - Deshmukh Hafsa; S. Chanda; Pradnya J. Prabhu (E-Journal of Chemistry)
A rapid and simple high performance liquid chromatography method was developed and validated at λ=275 nm for simultaneous determination of methocarbamol, paracetamol and diclofenac sodium (lamotrigine as an internal standard) from pharmaceutical preparation. The separation was performed using methanol: water: GAA, in the ratio of 400:600:05 (v/v) as the mobile phase. The detector response was linear in the range of 5 to 45 μg, 3.25 to 29.25 μg, 0.5 to 4.5 μg for methocarbamol, paracetamol and diclofenac sodium respectively. The percentage assay of methocarbamol, paracetamol and diclofenac sodium was found between 100, 99.76 and 99.31% respectively. The described method has the advantage of being rapid and easy hence it can be applied for routine quality control analysis.